PPO.14 A 5 Year Retrospective Analysis of Stillbirth Trends in a Large Obstetric Unit – will lives be saved with increasing resources towards identification of and intervention in small for gestational age foetuses?. (9th June 2014) - Neville, G; Foley, M
Abstract : Recent guidelines suggest intensive monitoring and consideration for delivery at 37 weeks for all small for gestational age (SGA) foetuses. 1 Adopting such an approach has considerable resource implications. This study aimed to retrospectively analyse trends in stillbirth in a major obstetric unit to ascertain if adhering to suggested guidelines would be likely to avert these tragedies. A retrospective analysis of all deliveries in the unit from 2008–2012 inclusive was conducted. Using the GROW (Gestation Related Optimal Weight) calculator; the growth centile of each delivered infant was calculated. The risk of stillbirth per 10, 000 ongoing pregnancies was calculated for each week of gestation > 24 weeks. The risk of stillbirth in SGA foetuses was calculated per 10, 000 ongoing SGA pregnancies. Out of 47015 recorded births; there were 178 stillbirths >24 weeks gestation in the 5 year period. 63 stillbirths occurred at or after 37 weeks gestation. The cumulative risk of stillbirth rose from 1.1/10 000 deliveries at 28 weeks, 1.5/ 10000 at 34 weeks, 3.4/10 000 at 37 weeks, 3.6/ 10 000 at 40 weeks and 13.5/ 10 000 at 41 weeks. In the SGA group, the risk of stillbirth rose from 3.1/10 000 deliveries at 28 weeks, 9.87/ 10 000 at 34 weeks, 12.79/10 000 at 37 weeks, 17.36/ 10 000 at 40 weeks and 47.58/10 000 at 41 weeks. SGA foetuses are at increased risk of stillbirth at all gestational ages but particularly after 40 weeks gestation. Further clarification is necessary on the optimal time for intervention. Reference: 1 http://www.rcog.org.uk/womens-health/investigation-and-management-small-gestational-age-fetus-green-top-31